China's New Sources of Economic Growth Human Capital, Innovation and Technological Change Vol. 2 - Song, Ligang; Garnaut, Ross; Fang, Cai; Johnston, Lauren (ANU Press, 2017)
China's efforts in searching for new sources of growth are increasingly pressing given the persistence of the growth slowdown in recent years. This year's book elucidates key present macroeconomic challenges facing China's economy in 2017, and the impacts and readiness of human capital, innovation and technological change in affecting the development of China's economy. The book explores the development of human capital as the foundations of China's push into more advanced growth frontiers. It also explores the progress of productivity improvement in becoming the primary mechanism by which China can sustain economic growth, and explains the importance of China's human capital investments to success on this front. The book demonstrates that technical change is a major contributor to productivity growth; and that invention and innovation are increasingly driving technical change but so far lumpily across regions, sectors and invention motivations. Included are chapters providing an update on reform and macroeconomic development, educational inequality, the role of intangibles in determining China's economic growth, and China's progress in transitioning towards being an innovative country. The book also covers the regional dimension of innovation and technological progress by sector: in agricultural productivity, renewable energy and financial markets. Chapters on trade, investment, regional cooperation and foreign aid explore further the mechanisms through which technological change and innovative activities are emerging locally and internationally.